STUDY ON OCCURRENCE OF ESBL AND AMP C BETA LACTAMASE AMONG GRAM NEGATIVE CLINICAL ISOLATES FROM GOVERNMENT HOSPITAL, MANGALORE - NEHA,; ABHISEK ROUTRAY,; SHALINI SHENOY, (International Journal of Pharma and Bio Sciences, 2014)
Resistant bacteria have emerged and established themselves worldwide as a threat to the favourable outcome of common infections in community and hospital settings. Beta lactamase production by several gram negative and gram positive organisms is perhaps the most important single mechanism of resistance to penicillins and cephalosporins. ESBL and AmpC beta lactamases are typically associated with multiple antibiotic resistances, leaving few therapeutic options. In this study, a total of 116 patient samples were evaluated for occurrence of ESBL and AmpC by Combination disk test and Modified three dimensional test respectively. 58.1% of isolates were ESBL producers, 23.3% were AmpC producers and 15.5% were both ESBL and AmpC producers.